2019
DOI: 10.2217/bmm-2018-0423
|View full text |Cite
|
Sign up to set email alerts
|

Association of Lymphocyte to Monocyte Ratio and Risk of In-Hospital Mortality in Patients with Acute Type A Aortic Dissection

Abstract: Aim: The aim of the study was to evaluate the relationship between lymphocyte to monocyte ratio (LMR) at admission and in-hospital mortality of patients with acute type A aortic dissection (AAAD). Patients & methods: We enrolled 536 patients with AAAD between June 2013 and December 2017. Patients were divided into two groups: the deceased group and the survival group. Results: In multivariable analysis, the association between LMR and in-hospital mortality was still significant. When the Q4 was set as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 27 publications
0
27
0
Order By: Relevance
“…Both lymphocyte to monocyte ratio (LMR) and lymphocyte to neutrophil ratio (LNR), obtained from routine blood tests at admission, are readily available inflammatory biomarkers [8,9]. Previous studies have found that LMR and LNR both were good predictors of worse outcomes in patients with AAAD [10,11]. However, the comparative predictive values of LMR and LNR are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Both lymphocyte to monocyte ratio (LMR) and lymphocyte to neutrophil ratio (LNR), obtained from routine blood tests at admission, are readily available inflammatory biomarkers [8,9]. Previous studies have found that LMR and LNR both were good predictors of worse outcomes in patients with AAAD [10,11]. However, the comparative predictive values of LMR and LNR are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…We hold that our study is distinct and meaningful, although some previous studies have reported better value ROC compared to HCO3 − in our study. 3,4,13 In these studies, the outcomes were in-hospital mortality and hospital complications such as aortic rupture, mechanical ventilation, renal dysfunction and visceral hemorrhage. In contrast, survival time and longer-term mortality (30 days, 90 days, 1 year and 5 years) were set as our outcomes in this study.…”
Section: Discussionmentioning
confidence: 99%
“…2 Hence, identification of simple biomarkers for evaluating the prognosis of AAD plays a vital role in risk stratification in this kind of patient. Previous studies have shown that lymphocyte-to-monocyte ratio (LMR), 3 hypotensive systolic blood pressure, 4 N-terminal pro-brain natriuretic peptide, 5 C-reactive protein, 6 cardiac troponin 7 and serum fibrinogen level 8 were associated with the prognosis of patients with AAD; however, the studies above mainly used in-hospital mortality as outcomes. Effective variables to predict the prognosis of AAD are still lacking in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…The coagulation system is activated by extensive in ammation and the reverse is also true via crosstalk 16 . Attention have been focused on the prognostic value of individual indicators such as MLR and NLR for ATAAD in previous studies 17,18 , which is unable to obtain an ideal prediction e cacy. New research demonstrates that ATAAD results from a combination of in ammation and thrombosis 19 .…”
Section: Disscussionmentioning
confidence: 99%